2022
DOI: 10.1002/saj2.20422
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term grassland restoration exerts stronger impacts on the vertical distribution of labile over recalcitrant organic carbon fractions in Mollisols

Abstract: Land use change influences soil organic carbon (SOC) distribution in soil matrix.Conversion of cropland to grassland or forestland has the potential to sequester more carbon and influence the carbon allocation. Soil carbon sequestration happens within different physical and chemical fractions. This study aimed to investigate the vertical distribution of SOC fractions under 29-yr of cropland, grassland, and forestland of a typical Mollisol and to derive specific factors for SOC fraction changes associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Conversion of cropland to grassland or forestland has the potential to sequester more C and change C allocation in varied C fractions. A 29‐yr field experiment on Mollisols of Northeast China demonstrated that conversion of cropland to grassland and forestland increased OC accumulation in soil profiles, especially at the 0‐to‐40‐cm depth (Hao et al., 2022). Long‐term grassland restoration exerted greater impacts on the labile OC than recalcitrant OC fractions through larger OC inputs from plant roots.…”
mentioning
confidence: 99%
“…Conversion of cropland to grassland or forestland has the potential to sequester more C and change C allocation in varied C fractions. A 29‐yr field experiment on Mollisols of Northeast China demonstrated that conversion of cropland to grassland and forestland increased OC accumulation in soil profiles, especially at the 0‐to‐40‐cm depth (Hao et al., 2022). Long‐term grassland restoration exerted greater impacts on the labile OC than recalcitrant OC fractions through larger OC inputs from plant roots.…”
mentioning
confidence: 99%